THE INFLUENCE OF LEARNING CARD SORT STRATEGY ON HISTORY LEARNING ACHIEVEMENT OF CLASS XI STUDENTS STATE HIGH SCHOOL 1 OF LHOONG ACEH BESAR - Rika Rahmalia; T Abdullah; Nurasiah . (Universitas Syiah Kuala, 2018)
The study, entitled